(untitled) - Gellissen, Gerd (Weinheim, 2005)
Includes bibliographical references and index
Keywords: Genetic vectors; Recombinant microorganisms; Recombinant proteins; Bacteria; Eukaryotic Cells; Technology, Pharmaceutical -- methods; Công nghệ dược phẩm -- Phương pháp; Vectơ di truyền; Vi sinh vật tái tổ hợp; Protein tái tổ hợp; Tế bào nhân thực; Vi khuẩn